Differences in motivation of food festivals visitors – A view from the Czech Republic - Krajíčková, Aneta; Šauer, Martin (Geographica Pannonica, 2018)
Gastronomy festivals are one of the fastest growing sectors of tourism and their importance for any destination is undeniable. The significance of the supply side attracts much more attention in research in contrast to the demand side in spite of the fact that knowing the customers and their motivation is the key for most aspects of realization and marketing of a festival. The main topic of this article are components of motivation to attend a festival that were obtained from self-administered questionnaires and categorized into dimensions of motivations. The dimensions are Taste, Experience, Social Status, Change, People, Family and Inspiration and they are studied in context of socio-demographic characteristics of the festivals attendees. This article compares two events held in the Czech Republic– PivniFest in Pilsen and Valtice Wine Markets. The results show primarily a distinct perception of festivals in terms of dimensions Family and Experience and the influence of education and marital status on the motivation.
Keywords: Differences in motivation; food tourism; food festivals; gastronomy motivation; tourism